Assessing European Union standardization: a descriptive analysis of voluntary ex ante transparency notices. Issue 1 (9th April 2021) - Prier, Eric; McCue, Clifford; Boykin, Emily A.
Abstract : Purpose: This study aims to empirically assess the standardization of using voluntary ex ante transparency notices to announce the awards of noncompetitive large-value contracts. Design/methodology/approach: Based on open data published in the Official Journal of the European Union, a pooled cross-sectional research design is used to determine the level of standardized use of noncompetitive contracting by member states. Findings: Findings suggest little evidence of standardization when publicizing direct contract awards, which might warrant remedial measures for promoting standardization by the EU. Moreover, France was found to be a major outlier in the prevalence of using non-competitive direct contract awards procedures. Social implications: Maintenance of the European Union is predicated on free, transparent and open competition among member states, and this can only be maintained if each member state transposes EU standards into their national laws. Originality/value: Findings suggest little evidence of standardization when publicizing direct contract awards, which might warrant additional remedial measures promoting consistency across the EU. Moreover, France was found to be a major outlier in the prevalence of using non-competitive direct contract awards procedures.